2011
DOI: 10.1002/bjs.7384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postconditioning on mitochondrial dysfunction in experimental aortic cross-clamping

Abstract: Ischaemic postconditioning protects skeletal muscle mitochondria against ischaemia-reperfusion injury by reducing oxidative stress and preserving antioxidant defence in an experimental model. Mitochondrial protection to reduce reperfusion injury in clinical vascular surgery may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 79 publications
6
56
0
Order By: Relevance
“…Such post-conditioning has been shown to reduce reperfusion-induced injury on occlusion of other vascular beds. 33 Third, we measured mitochondrial activity after gut IR in liver only. A multi-organ approach is severely hampered by the need to extract mitochondria from fresh tissue and measure oxygen consumption immediately.…”
Section: Discussionmentioning
confidence: 99%
“…Such post-conditioning has been shown to reduce reperfusion-induced injury on occlusion of other vascular beds. 33 Third, we measured mitochondrial activity after gut IR in liver only. A multi-organ approach is severely hampered by the need to extract mitochondria from fresh tissue and measure oxygen consumption immediately.…”
Section: Discussionmentioning
confidence: 99%
“…With reoxygenation, the respiratory chain of undamaged mitochondria produces ATP and the mitochondrial membrane potential is recovered. However, in cells subjected to ischemia, reperfusion further alters the activity of mitochondrial complexes I-IV as described in experimental models and PAD (28,108,146,147,176,179). The impaired function decreases ATP synthesis (Fig.…”
Section: ϩmentioning
confidence: 89%
“…Besides the heart (Skyschally et al,2009), postconditioning is also effective in salvage of ischemic skeletal muscle from reperfusion injury and the mechanism likely involves inhibition of opening of the mPTP and/or reduced oxidative stress (Szijarto et al,2009;Tsubota et al, 2010;Park et al, 2010;Guyrkovic et al, 2011;Mc Allister et al, 2008;Charles et al, 2011). There are few human studies, but it has been showed that postconditioning by intermittent early reperfusion reduces ischemia/reperfusion injury, that might depend on K(ATP) channel activation, and is mimicked by inhibition of the mPTP at reperfusion (Okorie et al, 2011).…”
Section: Ischemic Pre-and Post-conditioningmentioning
confidence: 99%